2021
DOI: 10.3389/fpsyt.2021.653821
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Postmortem Profiling of Inflammatory Mediators Expression Revealed Post-inflammatory Alternation in the Superior Temporal Gyrus of Schizophrenia

Abstract: Recent studies have lent support to the possibility that inflammation is associated with the pathology of schizophrenia. In the study of measurement of inflammatory mediators, which are markers of inflammation, elevated inflammatory cytokine levels in the brain and blood have been reported in patients with schizophrenia. Several postmortem brain studies have also reported changes in the expression of inflammatory cytokines. However, it is not clear how these elevated inflammatory cytokines interact with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Inflammation is considered to play a crucial role in the pathogenesis of schizophrenia. A postmortem study revealed decreased interleukin (IL)-1α and interferon (IFN)-ɣ-inducible protein 10 expression as well as increased IFN-α expression in the superior temporal gyrus of patients with schizophrenia, 58 suggesting a direct association of inflammatory markers with the disease. Since then, a variety of inflammatory markers have been assessed in different types of biospecimens, including peripheral blood and cerebrospinal fluid (CSF).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation is considered to play a crucial role in the pathogenesis of schizophrenia. A postmortem study revealed decreased interleukin (IL)-1α and interferon (IFN)-ɣ-inducible protein 10 expression as well as increased IFN-α expression in the superior temporal gyrus of patients with schizophrenia, 58 suggesting a direct association of inflammatory markers with the disease. Since then, a variety of inflammatory markers have been assessed in different types of biospecimens, including peripheral blood and cerebrospinal fluid (CSF).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the FOS family regulates the proliferation, transformation, differentiation, and apoptotic death of cells 65 . Based on upstream transcription factor analysis and high-throughput gene studies, FOSL1 implicates in SCZ through various mechanisms, such as influencing accessible chromatin regions and connecting to neuroinflammation signaling cascades 66 68 . SLC7A5 , also known as LAT1 , encodes a large amino acid transporter located in the blood–brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…However, an elevated level of IL-1α was found in patients with schizophrenia with metabolic syndrome even after 6 weeks of treatment with atypical antipsychotics [43]. The decreased expression of IL1-α and interferon-gamma-inducible protein (IP)-10 was found in patients with schizophrenia [44]. As mentioned, they conjectured that there was a suppressed common upstream pathway.…”
Section: Schizophrenia and Il-1αmentioning
confidence: 98%